Peran Perceived Value Dalam Memediasi Pengaruh Green Marketing Terhadap Loyalitas - IA Cynthia Saisaria Mandasari; Ade Ruly Sumartini (UNHI Press, 2020)
Every component of society began to worry about environmental pollution that could cause environmental damage. Concern about this is demonstrated by starting to use environmentally friendly products and pay attention to business activities carried out by companies around them. Seeing the current public concern for the environment makes business people start doing green marketing. One company that applies green marketing is Starbucks Coffee through Tumbler products. This research contributes ideas for SMEs in the field of beverage culinary to do green marketing to care for the environment and increase customer loyalty. Data collection using a questionnaire distributed directly to the object of research. The population in this study was Starbucks Coffee Tumbler users in Denpasar with a sample of 75 respondents. Data analysis techniques using path analysis (path analysis) and Sobel test.